Antineutrophil cytoplasm antibodies directed against myeloperoxidase augment leukocyte-microvascular interactions in vivo. - LITTLE, MARK (My University, 2005)
Systemic small vessel vasculitis is associated with antineutrophil cytoplasm antibodies (ANCAs). While there is mounting in vitro evidence to suggest that ANCAs are capable of enhancing leukocyte-endothelial interactions, no in vivo evidence for this has been provided. In this study a novel rat model of ANCA-associated experimental autoimmune vasculitis (EAV), induced by immunization with human myeloperoxidase (MPO), was used to analyze directly the potential effect of ANCAs on leukocyte-venular wall interactions in vivo as observed by intravital microscopy. These rats developed anti-MPO antibodies directed against rat leukocytes, showed pathologic evidence of small vessel vasculitis, and had enhanced leukocyte adhesion and transmigration in response to the chemokine Groalpha (CXCL1 [CXC ligand 1]). Passive transfer of immunoglobulin from rats with EAV to naive rats conferred enhanced adhesion and transmigration responses in the recipients. Furthermore, rats with EAV and recipients of ANCA-positive immunoglobulin developed extensive microvascular injury, as manifested by mesenteric hemorrhage, in response to CXCL1. This study provides the first direct in vivo evidence for the ability of ANCAs to enhance leukocyte-endothelial interactions and cause microvascular hemorrhage, thereby providing a mechanism by which ANCAs could exert pathogenic effects in systemic vasculitis.
PUBLISHED
Keywords: vasculitis; Immunology, Inflammation & Infection